Moral and Democratic Society System in Twain’s The Man Who Corrupted Hadleyburg - Ali, Muhammad Ilham; Tatipang, Devilito Prasetyo (Jurnal Lingua Idea, 2023)
This article sought to explore moral and democratic society systems within Mark Twain's short story "The Man That Corrupted Hadleyburg" using a descriptive methodology. The source of data in this research was the text of the short story itself, while to support the data, the writers encompassed relevant information related to the research, including literary theory and sociological perspectives on literature. The data collection process involved in-depth reading, transcription of pertinent quotations from the story to support the research, and systematic categorization. Through genetic structuralism as the analytical framework, this study revealed the moral criticism and democratic society system as the central themes, manifesting through key characters such as Edward Richard, Reverend Burgess, and other supporting figures. In Twain's "The Man Who Corrupted Hadleyburg," a profound exploration of moral criticism and democratic societal systems unfolds. The narrative delves into the intricacies of character morality, exposing the vulnerabilities of individuals and the democratic decision-making processes within the framework of Hadleyburg's society. The reactions of Hadleyburg's residents to the sudden influx of gold served as a noteworthy concluding point, shedding light on the broader societal implications within the narrative. In essence, this research illuminates the multifaceted layers of social criticism embedded in "The Man That Corrupted Hadleyburg," offering a nuanced understanding of the moral, societal, and individual dimensions explored by Mark Twain in this literary work.